2021
DOI: 10.1007/s13595-021-01064-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic gains in wood property can be achieved by indirect selection and nondestructive measurements in full-sib families of Japanese cedar (Cryptomeria japonica. D. Don) plus tree clones

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Similarly, negative correlations between growth traits and wood quality traits have been reported in several other pine species, such as Pinus contorta (Hayatgheibi et al 2017(Hayatgheibi et al , 2019, Pinus radiata (Wu et al 2008) and Pinus sylvestris (Hong et al 2014(Hong et al , 2015. In contrast, Larix kaempferi presented a positive correlation between diameter and BD (Fukatsu et al 2015), and diameter in Cryptomeria japonica was positively correlated with both BD and MOE (Yasuda et al 2021). Studies of P. radiata indicate that the higher the MOE d , the higher the tree slenderness (TS) (Lasserre et al 2008;Kimberley et al 2015;Watt and Trincado 2019).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Similarly, negative correlations between growth traits and wood quality traits have been reported in several other pine species, such as Pinus contorta (Hayatgheibi et al 2017(Hayatgheibi et al , 2019, Pinus radiata (Wu et al 2008) and Pinus sylvestris (Hong et al 2014(Hong et al , 2015. In contrast, Larix kaempferi presented a positive correlation between diameter and BD (Fukatsu et al 2015), and diameter in Cryptomeria japonica was positively correlated with both BD and MOE (Yasuda et al 2021). Studies of P. radiata indicate that the higher the MOE d , the higher the tree slenderness (TS) (Lasserre et al 2008;Kimberley et al 2015;Watt and Trincado 2019).…”
Section: Introductionmentioning
confidence: 68%
“…Given their importance to the timber industry (Bacher and Krzosek 2014), a lot of literature has been published on these traits. In general, both traits are strongly and positively correlated with each other in conifers (Baltunis et al 2007;Hong et al 2014;Yasuda et al 2021) but, usually, negatively correlated with yield traits such as growth and form. Determining how BD and MOE behave with respect to other traits is critical to improving multiple traits simultaneously in a breeding program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the seedling population has now been drastically reduced, and parental information could not be recovered. Because the recent research in C. japonica breeding has shown that clonal value could potentially be used as a proxy for the breeding value [52], the present study utilized the parental clonal value for the prediction of the clonal value of the offspring. To obtain the mid-parent value, the parents and their clonal values for the traits of interest must be known.…”
Section: Pedigree-based Prediction Using Mid-parent Valuesmentioning
confidence: 99%
“…Utilising wood not only enhances carbon sequestration in forests but also aligns with the principles of a circular economy, contributing to the goal of net-zero carbon emissions. Japanese cedar ( Cryptomeria japonica (L.f.) D. Don) is a prominent plantation tree species in East Asia [ 1 , 2 ]. Its extract exhibits excellent biological activity and can be used as a natural insecticide, wood preservative, fungicide, as well as in health care and medical products [ 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%